Experience of the health promotion clinics in Aseer region, Saudi Arabia - Abdullah M Al-Shahrani; Yahia M Al-Khaldi (Wolters Kluwer Medknow Publications, 2011)
Context: Health promotion is the most important element of primary health care. Therefore, it is essential for the health team to apply such activity. Objective: To describe a newly established health promotion clinic at primary health care centers, in Abha city, KSA. Materials and Methods: The study was conducted during the year 2009. The files of 429 individuals were reviewed after one year from attending the health promotion clinics in Abha city, KSA. Master sheet was designed based on the relevant items of the file. The health promotion services used in the study were based on the recommendation of the relevant guidelines. Data entry and analysis was carried out using Statistical Program for the Social Sciences (SPSS). P-values less than 0.05 were selected for statistical significance. Results: After one year, the percentage of the individuals who intake imbalanced diet and did not perform any type of physical activity was more than 90% while 8% are currently smokers and 14% had depression. Clinical examination and investigation revealed that more than one quarter of our subjects were overweight. Obesity was 42% in males versus 51% in females (P<0.04). Pre-hypertension and hypertension were detected among 44 and 12% respectively. About one fifth of our subjects had pre-diabetes 21% and 3% were confirmed to have diabetes mellitus. Diet and physical activity counseling was given to all participants while referral to concerned clinics was done for individuals who suffer from high blood sugar, abnormal lipid profile, obesity and depression. Conclusion: This study demonstrated that health promotion clinics provided by trained professional health care team can be used as a new approach for early detection and management of the common health problems in primary health care centers.